High resolving power electrospray drift tube ion mobility spectrometer with heated desolvation tube - Boillat, Marc-Aurèle; Hauser, Peter C. (Analytica chimica acta, 2025)
The separation performance of drift tube ion mobility spectrometers is usually relatively weak with resolving powers well below 100. Improving this aspect requires, besides the optimization of other parameters, the challenging increase of the drift voltage as deduced from fundamental equations describing the broadening of a drifting ion swarm. We recently succeeded in constructing an improved high voltage instrument equipped with an electrospray source capable of analysing liquid samples with resolving powers above 200. This instrument was further perfected with a newly developed heated desolvation tube guiding the ions to the injection gate. The electrospray desolvation process was thus enhanced while the separation region was maintained at room temperature to keep diffusional band broadening to a minimum. A further modification was also made to the detector circuitry in order to reduce its noise. To demonstrate the performance of the instrument several challenging ion mixtures, including two herbicides, a polymer mixture, and isomers of carnitine esters were successfully separated and detected. The resolving powers, calculated from the arrival time and peak width at half height, ranged from 123 to 228. The latter value represents 96 % of the theoretically achievable resolving power at the working drift voltage of 24.1 kV. Stand-alone electrospray ion mobility spectrometry is not often used and has not yet been developed to its full potential. The results with improved resolving powers demonstrate its capability as a simple technique for the analysis of liquid samples, which may often serve as a lower cost alternative to chromatography or mass spectrometry. [Display omitted] •A new ion mobility instrument was constructed with a heated desolvation tube.•Resolving powers ranged between 123 and 228.•Isomers of carnitine esters were separated.•Identity of the species was supported by mass spectrometry.